Synthesis, photophysical, photochemical and SO2 sensing properties of ball-type phthalocyanines substituted with carboxyl groups - Canlica, Mevlude; Omur, Birsel Can; Salih, Bekir (ELSEVIER, 2019)
Ball-type phthalocyanines substituted with carboxyl group at non-peripheral positions were synthesized and characterized by elemental analysis, Fourier-transform infrared, H-1 nuclear magnetic resonance, and electronic spectroscopies and mass spectrometry. The fluorescence quantum yields and corresponding lifetimes of singlet and triplet states were determined. It was found that the obtained lifetime of triplet states ranges from 80 to 820 mu s for the complexes. In order to get more detailed information about the charge transport mechanism and SO2 sensing potential of these compounds impedance spectroscopy measurements were carried out. The estimated model parameters for ac conduction mechanism indicated that the correlated barrier hopping model is the best to represent the dependence of the frequency exponent on temperature for all compounds investigated. From the SO2 sensing test of the compounds it was found that compound 4b has great potential for use of SO2 sensing element.
Keywords: PHOTODYNAMIC THERAPY; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; Chemistry